UPAYA MENGURANGI KEMISKINAN DENGAN PEMBINAAN LUMBUNG 102 110 PANGAN DI DAERAH ISTIMEWA YOGYAKARTA - Raya, Alia Bihrajihant; Wastutiningsih, Sri Peni (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2005)
The research aims to identify organization which conducted guidance of local food storage in Yogyakarta Province and to identify guidance focus of local food storage in the process of poverty alleviation in Yogyakarta area. Basically the used method in the study was descriptive analytical method. Descriptive study has some goals that include description on situation or events or describe relationship among phenomenon, hypothetic examination, prediction making and also describe the implication from a problem that will be solved. Qualitative method has been done through 3 stages namely data reduction, data presentation and creating of conclusion. In Yogyakarta, 89ok of local food storages were included into simple local food storages. Characteristics of simple local food storage were lack of storage facilities, small scale enterprise and having social orientation. Generally, existence and experience in managing of local food storage in Yogyakarta has been done in average of 2 years. However guidance in optimizing the function of local food storage was relatively still low. Guidance process has been done by two institutions namely local government and local owned enterprise by subject matters focus on agriculture, business diversification of local food storage and organization. Subject matters of local food storage have been directed on business improvement of local food storage from social orientation into more economical orientation. Changes of business orientation became efforts in reducing of poverty through creation of local food storage.